SELF-TRACKING ‘FEMTECH’: COMMODIFYING & DISCIPLINING THE FERTILE FEMALE BODY - Roetman, Sara (AoIR Selected Papers of Internet Research, 2020)
This paper engages with feminist political economists to explore questions of affective labour and value-production in self-tracking technologies designed for the female body (‘femtech’). Self-tracking femtech is largely characterised by smartphone applications and smart devices that track user data relating to menstruation, fertility periods, sexual activity, ovulation, hormones, and health and wellbeing. This data can be collected through self-reporting or through automated transmission from sensory devices attached to the body. By reflecting on my own experiences with these technologies, this paper argues that users of self-tracking femtech perform the labour of reproducing our bodies and our affective relations in ways that are amenable to both capitalist and patriarchal structures of power. Situated within the broader shifts of care and social reproduction, self-tracking femtech can be understood as affective infrastructures that re-stabilise gender norms and continue to unevenly push the burden of reproduction onto a class of unpaid women. I explore the ways that affective experiences are shaped and modulated by self-trackers to (re)produce and discipline the fertile and sexual female body to be both a productive labouring body and heterosexually attractive feminine subjectivity. The labour of reproduction is further intertwined here with the labour of producing data for digital media industries that generates profit in the advertising marketplace. By examining co-constitutive and paradoxical forms of value at play, I dually situate self-tracking femtech within broader political struggles and locate the spaces of agency in our everyday entanglements with digital media technologies.